Carbon-ion radiotherapy induces ferroptosis and M1 macrophage polarization to inhibit the development of gastric cancer by downregulating DHODH - Wang, Yue; Cai, Hongyi (Frontiers in Medicine, 2025)
BackgroundCarbon-ion radiotherapy (CIRT) is an advanced form of high linear energy transfer (LET) radiotherapy that has demonstrated superior biological effectiveness compared to conventional photon therapy in the treatment of various malignancies; however, its role in gastric cancer remains unclear. Dihydroorotate dehydrogenase (DHODH), a key enzyme implicated in cancer progression, has been linked to tumor radiosensitivity. This study aims to investigate whether CIRT inhibits gastric cancer progression via the regulation of DHODH.MethodsHuman gastric cancer cell lines (HGC27, AGS) were treated with CIRT (0 Gy, 2 Gy, and 4 Gy). Cell viability, migration, and invasion were assessed with MTT and Transwell assays. Expression of ferroptosis-related markers and DHODH was evaluated using Western blotting and quantitative reverse transcription polymerase chain reaction (qRT-PCR). Macrophage polarization was assessed by flow cytometry after exposure to tumor-conditioned medium (CM). BALB/c nude mice were subcutaneously injected with AGS cells and randomly assigned to the control, CIRT, and DHODH+CIRT groups.ResultsIn vitro, CIRT suppressed DHODH expression and enhanced intracellular iron and reactive oxygen species (ROS) accumulation, promoting ferroptosis in gastric cancer cells. CM from irradiated cells increased the CD86+CD206− macrophage population and upregulated M1-associated cytokines. In vivo, CIRT significantly reduced tumor growth in xenograft models, and this effect was attenuated by DHODH overexpression. Tumor tissues from the CIRT group exhibited increased ferroptosis marker ACSL4 and reduced GPX4 expression, consistent with in vitro findings.ConclusionThese findings suggest that CIRT promotes ferroptosis and drives M1-like macrophage polarization through DHODH suppression. Targeting DHODH may enhance the therapeutic efficacy of CIRT in gastric cancer.